Research methods in business studies - Ghauri, Pervez N., 1948-; Grønhaug, Kjell; Strange, Roger (Cambridge : Cambridge University Press, 2020)
This accessible guide provides clear, practical explanations of key research methods in business studies, presenting a step-by-step approach to data collection, analysis and problem solving. Readers will learn how to formulate a research question, choose an appropriate research method, argue and motivate, collect and analyse data, and present findings in a logical and convincing manner. The authors evaluate various qualitative and quantitative methods and their consequences, guiding readers to the most appropriate research design for particular questions. Furthermore, the authors provide instructions on how to write reports and dissertations in a clearly structured and concise style. Now in its fifth edition, this popular textbook includes new and dedicated chapters on data collection for qualitative research, qualitative data analysis, data collection for quantitative research, multiple regression, and additional methods of quantitative analysis. Cases and examples have been updated throughout, increasing the applicability of these research methods across various situations.
Title from publisher's bibliographic system (viewed on 29 Jan 2020).
Keywords: elektronické knihy; electronic books; Management -- Research; Business -- Research